Striking a balance: The influence of work-related pressures on academicians’ mental health in Malaysian Higher Education - Sakarji, Siti Rosnita; Othman, Abdul Kadir; Omar, Siti Nur Zahirah (Journal of Islamic, Social, Economics and Development, 2025)
This study aims to examine the influence of job demands on the mental health of academicians in Malaysian public higher education institutions. A quantitative research design was employed, with data collected through a structured questionnaire distributed to academicians at public universities. The study specifically investigated the relationship between job demands comprising workload, role conflict, work-family conflict, and family-work conflict and mental health outcomes, including depression, anxiety, and stress. The data were analyzed using multiple regression analysis to identify significant predictors of mental health issues. The findings indicate that workload and work-family conflict are the primary contributors to poor mental health among academicians. These results highlight the urgent need for higher education institutions to address job demands by reducing excessive workloads, providing flexible work arrangements, and promoting a supportive work environment. Additionally, academicians are encouraged to adopt effective stress management techniques to cope with job-related challenges. This study emphasizes the critical role of managing job demands in preserving academicians' mental health and well-being.